Human's Relation with Others and the Universe in the Novel Syahadat Cinta by Taufiqurrahman Al-Azizy - Murdianto Murdianto; Titin Nur Taidah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Novel Syahadat Cinta by Taufiqurrahman Al Azizy is to photograph how humans relate to nature in depth. This research seeks to reveal the relationship between humans and fellow humans and the universe in the novel Syahadat Cinta by Taufiqurrahman al-Azizy. This research is a literature study (library research) with a mimetic approach. The data of this research is the relationship between humans and the universe. The data source for this research is the novel Syahadat Cinta by Taufiqurrahman Al-Azizy. Data collection techniques use documentation. At the same time, the data analysis technique uses content analysis. The results of this study indicate that The novel Syahadat Cinta by Taufiqurrahman Al-Azizy has the content of educating human relations with fellow human beings by cultivating good manners, being devoted to both parents, loving each other, apologizing, being generous and sincere. Educating human relations with the universe in the novel Syahadat Cinta by Taufiqurrahman Al-Azizy includes maintaining beauty and cleanliness and preserving ecosystems.